Is an ageing population impacting energy use in the European Union? Drivers, lifestyles, and consumption patterns of elderly households. (March 2022) - Pais-Magalhães, Vera; Moutinho, Victor; Robaina, Margarita
Abstract: The share of the elderly population is increasing, impacting countries' economic growth, energy use, carbon dioxide emissions, and sustainable development paths. This study analysed the effect of population ageing on residential energy consumption for the 28 member states of the European Union for the period 2005–2018, employing econometric methods. The Panel was further divided into groups that account for energy needs similarities based on the Heating and Cooling degree-days index. The variables used were directly linked to people aged 65 and over. Control variables related to efficiency measures were included to provide tailored measures for the elderly. The results show considerable variation between the Panel and the Groups, meaning that different heating and cooling energy needs ought to be considered when designing policies. The group with the highest energy needs for heating and cooling showed a superior performance concerning renewable sources and a higher propensity to invest in energy-saving measures. The contrary was observed for the groups with medium and low needs due to the loss of economies of scale. For the group with lowest energy needs, income inequality is a driver that mitigates energy use. Globally, this study highlights the urgent need to develop social and public policies at the EU level that take into account the significant increase in elderly, single households, their lifestyle effect, their lack of information on renewable energy options, or the finance and technology required to access it, and the differences found for each group of countries.